The Effect of Variable Distance and Moving Targets Training on Balasuga Academy Players’ Passing Accuracy - Novan Abdul Roman; Said Junaidi (Universitas Negeri Semarang, 2026)
This study examined the effect of variable distance and moving target training on football passing accuracy and compared it with conventional training. The study used an experimental method with a nonequivalent control group design. The sample consisted of 16 football school players divided into an experimental group and a control group using the ordinal pairing technique. The experimental group received variable distance and moving target training, while the control group followed conventional training. Passing accuracy was measured using a football passing accuracy test based on the football skills test developed by Subagyo Irianto. Data were collected through pretest and posttest measurements. Data analysis used descriptive statistics, normality tests, homogeneity tests, paired sample t tests, and independent sample t tests. The results show that variable distance and moving target training significantly improved passing accuracy with a t value of -9.029 and a significance value below 0.001. The analysis also shows a significant difference between the experimental and control groups with a t value of 3.870 and a significance value of 0.002. These results indicate that variable distance and moving target training are more effective than conventional training for improving football passing accuracy.